Antibacterial Efficacy of Casuarina Cunninghamiana Extracts Against Some Pathogenic Bacteria - Al-Hadad, Ayaat; AL-Zubaidy, Fatima. H. (Medical Science Journal for Advance Research, 2022)
The objective of study prepare extract of Casuarina cunninghamiana leave, fruit and bark against bacteria Staphylococcus aureus and Escherichia coli. Methods: collect and prepare sample ,phytochemicals , identifying antibacterial activity. Results: The results indicated to effect of bacteria having higher value of inhibition zone of leaves compared with fruit and bark . Methanolic extract proceed both hot water and ethanolic extract in its effect and increased activity of extracts with increased concentration (500,250.125,62.5)mg/ml .Conclusion: Methanoic extracts proceed both hot aqueous and ethanolic extracts in its antibacterial activity against G+ve than G-ve .